Network-coded secondary communication with opportunistic energy harvesting - Moritz, Guilherme Luiz; Baraldi Mafra, Samuel; Rebelatto, Joao Luiz; Demo Souza, Richard; Uchoa-Filho, Bartolomeu F.; Yonghui Li (International Symposium on Wireless Communication Systems, 2016)
We consider a cognitive wireless network with two energy-constrained secondary users (SUs) and a common secondary destination, where the SUs harvest energy from the transmitted signals of primary user (PU). We obtain closed-form approximations for the outage probability, the outage capacity and the optimum energy harvesting time of the proposed scheme. The analytical derivations are validated by numerical results.